In search of an oasis: a photovoice documentation of the water struggle in fragile & conflict-affected communities in Adamawa State, Nigeria - International Water Management Institute (International Water Management Institute, 2024)
Read our new #PhotoEssay, ‘In Search of an Oasis: A Photovoice Documentation of the Water Struggle in Fragile & Conflict Affected Communities in Adamawa State, Nigeria.’ Despite Nigeria’s growing economy, the country continues to contend with compound challenges related to fragility, conflict, and migration (FCM) and in Adamawa State, Northern Nigeria, water is scarce. Climate change is tightening its grip on Adamawa’s resources and ongoing conflict and the displacement of vulnerable communities into the state intensifies a desperate struggle for water. 📸 Supported by the Norwegian Government (@Norad) under ‘Learning Support for a Sub-Saharan Africa Multi-Country Climate Resilience Program for Food Security project,’ IWMI has been working in partnership with @WFP, under the @CGIAR ‘s #FCMInitiative, to highlight and explore the realities of water scarcity and to fragility. The partnership carried out a ‘Photovoice’ research project in which members of Adamawa State communities used photography to document their daily search for water. Photovoice is a participatory action research method in which photography and group dialogue are utilized to deepen the external understanding of community concerns. 🖥 Explore the work of the Adamawa State Photovoice project by reading our new photo essay in collaboration with @Dinovate and exploring community images from Adamawa. Over the next three weeks we will continue to share important stories from the region as we release a three-part video podcast series titled ‘The Water and Conflict Podcast’ featuring the researchers, communicators and community members who were intimately involved in the project. Make sure to keep an eye out for updates and tune in!